Environment and Economic Benefits through the Preference for More Open Commercial Policy - CHANCHAROENCHAI, Kanokwan; SARAITHONG, Wuthiya (Journal of Environmental Management and Tourism; Vol 12 No 7 (2021): JEMT Volume XII, Issue 7(55), Winter 2021DO - 10.14505/jemt.v12.7(55).05, 2021)
The objective of this paper is to explore the determinants of individuals ’ opinions about relaxed economic policy regime, whether more open economic activities benefit the country and its people . As this is a study at the micro level, thus questionnaire survey is conducted in Bangkok area . The binary analysis is employed to address the explanatory power of relevant variables . According to statistical tests, logit estimation is more accurate than the probit model. The estimated models indicate that, among other things, individuals ’ perception about the liberalization of economic regime seems to sustain the strongest cause for the issues regarding the gains from more open economic activities . Furthermore, the findings show the explanatory power of the Stolper - Samuelson Theorem and the environmental Kuznets curve hypothesis .